MORPHOLOGICAL CHARACTERISTICS OF MALAYSIAN NATIONAL CRICKET BATSMEN (International Journal of Physiotherapy, 2016)
Background: The purpose of this study was to examine the morphological characteristics and physical strength of the Malaysian cricket batsmen.Methods: Twenty four top order batsmen from the Malaysian senior, under-19s and under-16s cricket team were recruited for the study. Twenty six anthropometric, four somatotype and two physical strength variables were measured from all participants. Stature were measured by using stadiometer, calipers for skin-fold, non-stretch tape for girth, sliding caliper for segmental lengths and circumferences (breadths) and dynamometers for hand grip and back strength. Cater and heath (1990) equation was used to find the somatotype variables of height-weight ratio, endomorph, mesomorph and ectomorph. One way analysis of variance (ANOVA) was used to analyses significant between group differences in the variables.Results: The senior batsmen were significantly higher than under-19s and under-16s in body mass, relax and flex arm girths, forearm girth, chest girth, waist girth, calf girth, bi-acromial breadth, transvers breadth and hand grip strength. Both senior and under-19s batsmen were significantly higher than under-16s batsmen in arm span, total arm length, humerus and femur breadths. The under-16s batsmen were also significantly lesser than senior in hip girths, hand lengths and bi-ilocrist breadth, and from under-19s in sitting height and total leg length.Conclusion: Senior batsmen were significantly higher in the anthropometric measurement of girths, breadth and lengths than U-16 because of 10 years age difference. Future research is essential to confirm the relationship between the anthropometric characteristics of batsmen with the batting technique and performance.